The Readiness for Implementing a Baby-Friendly Hospital Initiative at PKU Muhammadiyah Gombong Hospital - Nurlaila Nurlaila; Eka Riyanti; Alfina Suci Fitriyani; Khusnul Dwi Haryani (Universitas Aisyah Pringsewu, 2023)
Breastfeeding practices for newborns require adequate support from the hospital, including its staff and policies. This concept can be implemented through a baby-friendly hospital initiative. This study aimed to identify the readiness for implementing a baby-friendly hospital initiative at PKU Muhammadiyah Gombong Hospital. A descriptive study was conducted among hospital staff in charge of newborn care as many as 85 people recruited using total sampling, and 101 postpartum mothers recruited using purposive sampling. The readiness for implementing a baby-friendly hospital initiative was examined through the knowledge and perceptions of the hospital staff and the practice of implementing the baby-friendly hospital, which were measured using questionnaires. Descriptive data analysis was carried out using STATA Version 16. The results showed that the majority of hospital staff had good knowledge and perceptions of the baby-friendly hospital initiative (97.65% and 74.12%, respectively). Seven of the 10 steps for successful breastfeeding had been implemented in the hospital, while the other three steps, i.e., skin-to-skin contact, immediate breastfeeding one hour after birth, and health workers’ recommendation of breastfeeding support to mothers, had not been carried out. It is concluded that PKU Muhammadiyah Gombong Hospital is ready to implement a baby-friendly hospital; however, training for hospital staff is still needed to prepare for its implementation. Abstrak: Praktik pemberian ASI pada bayi baru lahir memerlukan dukungan rumah sakit dan staffnya. Kebijakan rumah sakit juga harus mendukung praktik pemberian ASI. Konsep tersebut dituangkan dalam rumah sakit sayang bayi. Tujuan penelitian adalah mengidentifikasi kesiapan penerapan Rumah Sakit Sayang Bayi di RS PKU Muhammadiyah Gombong. Penelitian menggunakan metode deskriptif. Sampel penelitian adalah staff rumah sakit yang bertugas pada pelayanan bayi baru lahir sebanyak 85 orang diambil secara total sampling, serta ibu post partum sebanyak 101 orang yang diambil secara purposive sampling. Kesiapan penerapan rumah sakit sayang bayi dilihat melalui pengetahuan dan persepsi staff rumah sakit serta praktik penerapan rumah sakit sayang bayi yang diukur menggunakan kuesioner. Analisis data dekriptif menggunakan STATA Versi 16. Penelitian dilakukan di RS PKU Muhammadiyah Gombong. Hasil penelitian menunjukan sebagian besar staff rumah sakit memiliki pengetahuan dan persepsi yang baik (97,65 % dan 74,12%), 7 dari 10 langkah keberhasilan menyusui sebagian besar sudah dilakukan, terdapat 3 langkah yang dilaporkan belum dilakukan yaitu skin to skin kontak, menyusui segera 1 jam setelah lahir dan tenaga kesehatan merekomendasikan dukungan menyusui kepada ibu. Kesimpulan penelitian ini adalah RS PKU Muhammadiyah Gombong siap menerapkan rumah sakit sayang bayi. Pelatihan untuk staff rumah sakit diperlukan untuk menyiapkan pelayanan rumah sakit sayang bayi.